Combining periodic hydraulic tests and surface tilt measurements to explore in situ fracture hydromechanics. Issue 8 (10th August 2017) - Schuite, Jonathan; Longuevergne, Laurent; Bour, Olivier; Guihéneuf, Nicolas; Becker, Matthew W.; Cole, Matthew; Burbey, Thomas J.; Lavenant, Nicolas; Boudin, Frédéric
Abstract: Fractured bedrock reservoirs are of socio‐economical importance, as they may be used for storage or retrieval of fluids and energy. In particular, the hydromechanical behavior of fractures needs to be understood as it has implications on flow and governs stability issues (e.g., microseismicity). Laboratory, numerical, or field experiments have brought considerable insights to this topic. Nevertheless, in situ hydromechanical experiments are relatively uncommon, mainly because of technical and instrumental limitations. Here we present the early stage development and validation of a novel approach aiming at capturing the integrated hydromechanical behavior of natural fractures. It combines the use of surface tiltmeters to monitor the deformation associated with the periodic pressurization of fractures at depth in crystalline rocks. Periodic injection and withdrawal advantageously avoids mobilizing or extracting significant amounts of fluid, and it hinders any risk of reservoir failure. The oscillatory perturbation is intended to (1) facilitate the recognition of its signature in tilt measurements and (2) vary the hydraulic penetration depth in order to sample different volumes of the fractured bedrock around the inlet and thereby assess scale effects typical of fractured systems. By stacking tilt signals, we managed to recover small tilt amplitudes associated with pressure‐derived fracture deformation. Therewith, we distinguish differences in mechanical properties between the three tested fractures, but we show that tilt amplitudes are weakly dependent on pressure penetration depth. Using an elastic model, we obtain fracture stiffness estimates that are consistent with published data. Our results should encourage further improvement of the method. Key Points: A repeated periodic hydromechanical experiment is performed using surface tiltmeters to measure natural fracture deformation at three depths Stacking tilt signals significantly improves signal‐to‐noise ratios and enables detection of weak stress perturbation in fractures No dependence of tilt amplitude on period of test suggests that a fixed portion of fracture deforms regardless of pressure penetration depth